Teacher Strategies in Developing Speaking Skills for Class VI Students - Putri, Azaliya (Tekno - Pedagogi : Jurnal Teknologi Pendidikan, 2019)
This study aims to describe the strategies employed by teachers to enhance the speaking abilities of sixth-grade students at SDN 04/II Muara Bungo during the odd semester of the 2018/2019 academic year. Utilizing qualitative research with a descriptive approach, data collection involved observation, interviews, and documentation of the homeroom teachers of class VI. The findings indicate commendable speaking proficiency among students, facilitated by diverse teaching strategies. These encompass social skill development through discussions, model repetition, and interactive questioning; semantic skill enhancement via audio-visual aids like images and videos, alongside question-answer techniques; phonetic skill refinement through mobile audio-visual aids and interactive sessions; vocal skill improvement through revisiting reading materials and interactive sessions; as well as teachers employing effective speaking styles, utilizing standard language, appropriate gestures, and mastery of the subject matter. Additionally, teachers utilize oral assessments to evaluate students' speaking proficiency. In conclusion, the study affirms the teachers' success in fostering students' speaking abilities, encompassing social, semantic, phonetic, and vocal dimensions.